Cam Jansen and the chocolate fudge mystery - Adler, David A. (Adler, David A. Cam Jansen adventure, 1993)
When Cam Jansen and her friend Eric uncover a mystery while selling fudge door-to-door to raise money for the local library, Cam uses her photographic memory to foil a crime.